Can culture beat Covid‐19? Evidence that exposure to facemasks with cultural symbols increases solidarity. (25th January 2022) - Perach, Rotem; Limbu, Maliyana
Abstract: Facemasks have become integral to everyday life. We propose that exposure to facemasks with a solidarity‐related cultural symbol can activate cultural values such as mutual trust and increase corresponding interpersonal perceptions, thereby enhancing collective resilience in the Covid‐19 pandemic. In three (two of which preregistered) studies, we examined whether exposure to facemasks with a solidarity‐related cultural symbol predicts positive interpersonal perceptions, and whether this depends on death awareness. Across studies, exposure to facemasks with a cultural symbol (either pride flag or National Health Service) increased positive interpersonal perceptions, an index of solidarity, in people for whom this symbol represents a meaningful social identity. This was found whether participants were reminded of death, a neutral experience, or a negative experience. Importantly, in Study 3, exposure to facemasks with a solidarity‐related cultural symbol (vs. surgical) led to greater increases in positive interpersonal perceptions when death awareness was high. Together, our findings suggest that wearing facemasks with a cultural symbol that relates to solidarity can be a vehicle for shaping people's personality impressions of others. Applied directions for the activation of people's social identities via facemask selection to promote collective resilience in the Covid‐19 pandemic are discussed.